Inleiding in de psychologie - Langeveld, M. J. (Martinus Jan), 1905-1989; Kohnstamm, Philipp Abraham, 1875-1951; Linschoten, Johannes, 1925-1964; Van Parreren, C. F. (Carel Frederik), 1920-1991 (Groningen : J.B. Wolters, 1961)
Een uitgebreide kennismaking met de psychologie.